Analyze the Impact and Handling of Legal Actions on Bullying on Social Media Tiktok - Shinta Rahmalia Saputri; Arief Budiono (Dinasti Research, 2024)
Bullying on social media, including the TikTok platform, has become a pressing issue in the modern digital context. This research aims to analyze the impact and handling of legal actions on bullying on TikTok social media. This research method is empirical legal research. The primary and secondary data sources of this research are primary and secondary. The data collection techniques are interviews, questionnaires, and observation. The method of analyzing data obtained from research is processed and analyzed in a qualitative descriptive way, meaning that data analysis is based on what is obtained from the literature, both orally and in writing, then directed, discussed, and given an explanation with the applicable provisions and then concluded. The results of this study show that both victims and perpetrators have a negative impact from criminal acts of bullying—legal consequences for the perpetrators and legal protection for victims of cyber bullycyberbullyingd. The legal mechanism can handle legal acts of bullying on the internet, especially on TikTok social media, namely complaints on the TikTok social media platform. Bullying on social media can be sanctioned based on Law No. 11 of 2008 concerning Electronic Information and Transactions (UU ITE), updated with Law No. 19 of 2016. Suppose the act of bullying relates to insult or defamation. In that case, the perpetrator can be charged with the Criminal Code (KUHP) Articles 310 and 311 with the threat of imprisonment or a fine, depending on the severity of the case.